TAKING CARE OF THE SPINE AT THE COMPANY: THE PHYSICAL EDUCATION, CHIROPRACTIC, AND PUBLIC RELATIONSHIPPROFESSIONALS' LOOK (Fiep Bulletin - online, 2013)
Work has an important role in men's life. Besides being the source of its support, it also gives them the chance to feel useful, productive and valued. However, when performed under unsuitable conditions, it may cause several levels of danger to health, such as musculoskeletal pain. The “Taking care of the Spine at the Company” project tries to contribute to the improvement of the workers' quality of life and to the promotion of their health, in which the interdisciplinary look of the Physical Education, Chiropractic and Public Relations professionals transcends the labor practice, effectively helping in people's life and corroborating to the company's productivity. The pilot project took place from January to April, 2008 and involved the diagnosis and treatment, maintenance and prevention stages. Eight individuals that were evaluated through Corlett's Diagram, postural assessment, anamnesis and interviewed participated of the project. As main results, a significant decrease of the discomfort and pain levels (p